“Huge waves crash high 'gainst ragged shores”: Geo-Interpretation for Marine and Coastal Geotourism - Patrick James (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Abiotic, Biotic and Cultural environments can be best exploited for (geo)tourism with appropriate (geo)interpretation. Ragged and rocky shores, like those of the “Mermaids Song”, where “Huge Waves Crash” are found only where the sea meets the land. These common but always unique coastal zones include rocks and landscapes (abiotic), plant and animal ecosystems (biotic) and important human (cultural) and economic habitats. Marine coastlines, shallow intertidal zones and islands display magnificent features ranging from never ending beaches to soaring cliffs, fascinating shore platforms to enthralling estuaries and deep fjords to sparkling reefs. Coasts and shorelines provide a fundamental boundary between the land we live, work and play on and the vastly different largely uninhabited oceanic seascape. All coasts are intrinsically aesthetic and beautiful and provide a wealth of environments and opportunities for geotourism.